Time to onset of cannabidiol (CBD) treatment effect in Lennox–Gastaut syndrome: Analysis from two randomized controlled trials. (2nd April 2021) - Privitera, Michael; Bhathal, Hari; Wong, Matthew; Cross, J. Helen; Wirrell, Elaine; Marsh, Eric D.; Mazurkiewicz‐Beldzinska, Maria; Villanueva, Vicente; Checketts, Daniel; Knappertz, Volker; VanLandingham, Kevan
Abstract: Objective: To estimate time to onset of cannabidiol (CBD) treatment effect (seizure reduction and adverse events [AEs]), we conducted post hoc analyses of data from two randomized, placebo‐controlled, Phase 3 trials, GWPCARE3 (NCT02224560) and GWPCARE4 (NCT02224690), of patients with Lennox–Gastaut syndrome. Methods: Patients received plant‐derived pharmaceutical formulation of highly purified CBD (Epidiolex, 100 mg/ml oral solution) at 10 mg/kg/day (CBD10; GWPCARE3) or 20 mg/kg/day (CBD20; both trials) or placebo for 14 weeks. Treatment started at 2.5 mg/kg/day for all groups and reached 10 mg/kg/day on Day 7 and 20 mg/kg/day (CBD20 and matching placebo only) on Day 11. Percentage change from baseline in drop seizure frequency was calculated by cumulative day (i.e., including all previous days). Time to onset and resolution of AEs were evaluated. Results: Overall, 235 patients received CBD (CBD10 [GWPCARE3 only], n = 67; CBD20 [pooled GWPCARE3&4], n = 168) and 161 received placebo. Mean (range) age was 15.3 years (2.6–48.0). Patients had previously discontinued a median (range) of six (0–28) antiepileptic drugs (AEDs) and were currently taking a median of three (0–5) AEDs. Differences in drop seizure reduction between placebo and CBD emerged during the titration period and became nominally significant by Day 6 ( p = .008) for pooled CBD treatment groups. Separation between placebo and CBD in ≥50% responder rate emerged by Day 6. Onset of the first reported AE occurred during the titration period in 45% of patients (CBD10, 46%; CBD20, 52%; placebo, 38%). In patients with AEs, resolution occurred within 4 weeks of onset in 53% of placebo and 39% of CBD patients and by end of study in 63% of placebo and 61% of CBD patients. Significance: Treatment effect (efficacy and AEs) of CBD may occur within 1 week of starting treatment. Although AEs lasted longer for CBD than placebo, most resolved within the 14‐week period.